Role of on-farm/In situ conservation and underutilized crops in the wake of climate change - Sthapit, B.; Padulosi, S.; Mal, M. (2010)
Traditionally farmers use diverse crops, trees and wild plant species, livestock and aquatic species to sustain/enhance their livelihood. The use of diverse species and varieties enhances their adaptability and resilience capacity to changing environmental and economic conditions. Genetic diversity is a key element in farmers’ livelihood strategies particularly in areas under high ecological, climatic and economic stresses and risks. Global food security has become increasingly dependent on a limited number of varieties of a few major crops and in the wake of climate change, such a situation makes farmers more vulnerable with regard to their nutrition and income security. This paper aims to discuss the conceptual framework of on-farm/in situ conservation in adapting and mitigating climate change through an integrated system of diversified food production and land use. The role of on-farm/in situ conservation of crops is discussed along with its complementary advantages over ex situ conservation. Empowerment of farming communities is essential for effective in situ/on-farm conservation as the process encourages local level decision making on management of genetic resources. The paper also highlights community-based biodiversity management as a methodology to realize in situ/on-farm conservation through strengthening farmer seed systems, and promoting climate resilient integrated home garden production systems, especially underutilized crop species and carbon rich farming that support climate change actions. Implementation of biodiversity management approaches will require conducive policy environment in order to be truly effective and sustainable. Some relevant recommendations on how to best proceed towards a viable in situ/on - farm conservation system are also proposed.